STRATEGI PROMOSI KESEHATAN TERHADAP PENINGKATAN PERILAKU HIDUP BERSIH DAN SEHAT INDIVIDU PADA MASYARAKAT PERKEBUNAN DI WILAYAH PUSKESMAS SEI KIJANG KABUPATEN PELALAWAN - Sri Rezeki; Aras Mulyadi; Nopriadi Nopriadi (Jurnal Ilmu Lingkungan, 2013)
A clean and healthy lifestyle (CHL) is a health behavior which comes from one’s own awareness sothat a family member or a family could help him/herself with his/her health problems. To apply theCHL among the family or family members, the Health Department of Republic of Indonesia hascreated a health promoting program and has been decided as a flagship program. However, thenational health survey (2010) indicated that CHL nationally was still far from the minimal target(65%) of the year. The same thing goes to the implementation of the CHL in Sekijang Sub-district,Pelalawan Regency. Pelalawan Regency Health Profile shows that of 2010 households monitored,only 38% had had CHL inclusion. The present research seeks to investigate the correlation betweenthe community empowerment strategies and the individual CHL increase of families among theplantation community within the working area of Seikijang Community Health Center, PelalawanRegency. The data were calculated using Univariat and Bivariat analysis of Chi-Square. The resultsshow that there is a significant correlation between the community empowerment strategies and theindividual CHL increase in Seikijang Sub-district. The strategies shows that there is a significantcorrelation between advocacy and individual CHL, p value 0.007 < 0.005. then, there is a significantcorrelation between the community empowerment and the individual CHL increase, p-value 0.001 <0.05. There is a significant correlation between the atmosphere management and the CHL increase, pvalue 0.000 < 0.05 in Seikijang Sub-district. It is suggested that all parties be more proactive in theCHL program. The success of the program would have a positive impact on all parties, either on theHealth Office, the Community Health Center or on the community and each individual in a family.